2017
DOI: 10.1038/s41598-017-04098-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel synthetic approach of cerium oxide nanoparticles with improved biomedical activity

Abstract: Cerium oxide nanoparticles (CNPs) are novel synthetic antioxidant agents proposed for treating oxidative stress-related diseases. The synthesis of high-quality CNPs for biomedical applications remains a challenging task. A major concern for a safe use of CNPs as pharmacological agents is their tendency to agglomerate. Herein we present a simple direct precipitation approach, exploiting ethylene glycol as synthesis co-factor, to synthesize at room temperature nanocrystalline sub-10 nm CNPs, followed by a surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 74 publications
4
61
0
1
Order By: Relevance
“…Nanoceria are highly susceptible to aggregation and subsequent sedimentation in biological media. 33 The aggregation is believed to be caused by the presence of surface defects that increase with particle size reduction. 19 A formulation with poor colloidal stability results in the sedimentation of the nanoparticles in physiological media, consequently leading to the exposure of cellular monolayers to a higher concentration than the stated bulk concentration, and so compromising the reliability of in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoceria are highly susceptible to aggregation and subsequent sedimentation in biological media. 33 The aggregation is believed to be caused by the presence of surface defects that increase with particle size reduction. 19 A formulation with poor colloidal stability results in the sedimentation of the nanoparticles in physiological media, consequently leading to the exposure of cellular monolayers to a higher concentration than the stated bulk concentration, and so compromising the reliability of in vitro experiments.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Ce 3+ /Ce 4+ redox couple on the nanoparticle surface provides biological activity of cerium oxide nanoparticles [7]. Their action mechanism is similar to that of natural metalloenzymes that use transition metal ions, such as Fe 3+ , Cu 2+ , or Mn 3+ , to buffer reactive oxygen species in cells and tissues [7,8]. Due to this, nanosized cerium dioxide can be used in medical practice to combat chronic inflammation and pathology associated with oxidative stress, which includes cancer and neurodegeneration [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this, nanosized cerium dioxide can be used in medical practice to combat chronic inflammation and pathology associated with oxidative stress, which includes cancer and neurodegeneration [8]. It has been shown that one of the methods for increasing the stability of suspensions of nanosized cerium dioxide and correction of its biological action may be to cover the surface of nanoparticles of CeO 2 by biocompatible/organic polymers [8][9][10] and carboxylic acids [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…We hypothesize that there are defense mechanisms within U937 inflammatory‐like cells that help maintain viability at extreme cathodic voltages. Common inflammatory cells (i.e., macrophages, hepatocytes) synthesize reduced glutathione (GSH) when stimulated by oxidative stress . GSH is an antioxidant and functions as a ROS scavenger protecting the cell from ROS‐driven apoptotic processes such as reduction in cell growth, increased cell permeability and nuclear/internucleosomal DNA fragmentation .…”
Section: Discussionmentioning
confidence: 99%
“…Common inflammatory cells (i.e., macrophages, hepatocytes) synthesize reduced glutathione (GSH) when stimulated by oxidative stress. [47][48][49][50] GSH is an antioxidant and functions as a ROS scavenger 29 protecting the cell from ROS-driven apoptotic processes such as reduction in cell growth, increased cell permeability and nuclear/internucleosomal DNA fragmentation. 49 GSH has been shown to protect macrophage (RAW 264.7) and monocyte macrophage-like (U937) cells from apoptosis induced by triptolide, 51 7-ketocholesterol, 52 ceramide, 28 and tert-butylhydroperoxide (t-BOOH).…”
Section: Discussionmentioning
confidence: 99%